Spatial filtering of RF interference in radio astronomy. - Raza, J.
We investigate spatial filtering techniques for interference removal in multichannel radio astronomical observations. The techniques are based on the estimation of the spatial signature vector of the interferer from short-term spatial covariance matrices followed by a subspace projection to remove that dimension from the covariance matrix, and by further averaging. The projections will also modify the astronomical data, and hence a correction has to be applied to the long-term average to compensate for this. As shown by experimental results, the proposed technique leads to significantly improved estimates of the interference-free covariance matrix
Keywords: RF interference; Antenna arrays; Array signal processing; Astronomical data; Averaging; Interference removal; Interference-free covariance matrix; Interferometric radio astronomy; Long-term average; Multichannel radio astronomical observations; Short-term spatial covariance matrices; Spatial filtering; Spatial signature vector estimation; Subspace projection